Amino acid sequence and crystal structure of BaP1, a metalloproteinase from Bothrops asper snake venom that exerts multiple tissue-damaging activities - Watanabe, Leandra (2003)
BaP1 is a 22.7-kD P-I-type zinc-dependent metalloproteinase isolated from the venom of the snake Bothrops asper, a medically relevant species in Central America. This enzyme exerts multiple tissue-damaging activities, including hemorrhage, myonecrosis, dermonecrosis, blistering, and edema. BaP1 is a single chain of 202 amino acids that shows highest sequence identity with metalloproteinases isolated from the venoms of snakes of the subfamily Crotalinae. It has six Cys residues involved in three disulfide bridges (Cys 117-Cys 197, Cys 159-Cys 181, Cys 157-Cys 164). It has the consensus sequence H(142)E(143)XXH(146)XXGXXH(152), as well as the sequence C(164)I(165)M(166), which characterize the "metzincin" superfamily of metalloproteinases. The active-site cleft separates a major subdomain (residues 1-152), comprising four alpha-helices and a five-stranded beta-sheet, from the minor subdomain, which is formed by a single alpha-helix and several loops. The catalytic zinc ion is coordinated by the N(epsilon 2) nitrogen atoms of His 142, His 146, and His 152, in addition to a solvent water molecule, which in turn is bound to Glu 143. Several conserved residues contribute to the formation of the hydrophobic pocket, and Met 166 serves as a hydrophobic base for the active-site groups. Sequence and structural comparisons of hemorrhagic and nonhemorrhagic P-I metalloproteinases from snake venoms revealed differences in several regions. In particular, the loop comprising residues 153 to 176 has marked structural differences between metalloproteinases with very different hemorrhagic activities. Because this region lies in close proximity to the active-site microenvironment, it may influence the interaction of these enzymes with physiologically relevant substrates in the extracellular matrix.